La gestión del desempeño laboral: El efecto mediador del mindfulness entre el capital psicológico y el autoliderazgo - Bazán Tejada, Carlos Armando (2024)
This research explores the effect of psychological capital on self-leadership, and the mediation of mindfulness in this relationship. To such aim, structural equation modeling is used to validate the research hypothesis in a sample of 100 participants from companies from a variety of economic sectors. The results confirmed that the psychological capital maintains a positive and meaningful relationship with self- leadership and mindfulness, respectively. In addition, mindfulness maintains a positive and meaningful correlation with self-leadership. Finally, the research evidenced the complementary mediation of mindfulness in the relationship between psychological capital and self-leadership. These findings reveal aspects that contribute to the improvement of employees’ performance by validating the relationship among these three constructs in an empirical and integral fashion, even when no studies on such relationship are available mainly in Latin American countries. Surveys on the constructs under study are paramount for organizations since they allow to identify factors that contribute to the improvement of their employees’ performance.